Thermal stress in buffalo bulls (Bubalus bubalis): Evaluation of reproductive characteristics - Chacur, M. G.M. [UNESP]; Oba, E. [UNESP]; Ferreira, J. C.P. [UNESP]; Velloso, N. M. [UNESP] (My University, 2010)
The objective of the experiment was to measure the changes produced by heat on reproductive efficiency of buffalo bulls. For this, we used eight male crossbred (Murrah x Mediterranean), with approximately three years old. The animals were housed in a climate chamber and subsequently divided into two groups: control (CG) and heat stress (SG). After an adjustment period, bulls of SG were subjected to temperatures of 39 ° C, while the CG were maintained at room temperature of 22.5 ° C for a period of 54 days. We observed the reaction time (time of courting the female until ejaculation) of each animal, as well as the number of false mating until the mating be successfully performed. The perimeter and consistency of the testes and seminal characteristics were assessed weekly. In the same period and frequency, ultrasound scans were performed to measure the length and width of the testis, epididymis and spermatic cords. Under the experimental conditions, the only parameter evaluated that showed statistical difference between treatments was the testicular consistency, and SG animals displayed less consistency than those of CG.
Keywords: Buffalo; Heat stress; Mating behaviour; Semen